The effect of partial rootzone drying and foliar nutrition on water use efficiency and quality of table grape cultivars Crimson seedless and Dauphine - Van Zyl, Tinake (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Viticulture and Oenology))--University of Stellenbosch, 2007.